Flim Andragogy (2023): Identity Crisis and Power Shift in Indonesian Cinema - Sukmawati, Ni Luh Ayu (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
The phenomenon of posthumanism in Indonesia is no longer merely a theoretical discourse, but has become an everyday experience that reshapes social relations, identity, and human existence in the digital era. This study aims to examine how Wregas Bhanuteja's film Andragogy (2023) represents the dynamics of power in posthuman cinema through visual and narrative studies, with the Actor-Network Theory (ANT) approach from Bruno Latour and Jacques Lacan's gaze theory. The results of the study show that the virality of Bu Prani's video in the film functions as a non-human actor who has agency in shaping public opinion, mobilizing social networks, and distributing power. Social media is not only a space of representation, but also regulates social narratives that oppress individuals. Bu Prani loses control over her own identity, trapped in the logic of algorithms and collective power exercised by netizens through the mechanisms of gaze and méconnaissance. Through visual framing that shows how Bu Prani's personal space is reduced and her narrative is constructed by digital social networks, this film highlights the crisis of the subject in the posthuman era. Andragogy is not only an aesthetic critique of the post-pandemic era, but also reflects how power has shifted from humans to digital objects that are able to significantly modulate social life. The findings of this study emphasize that in posthuman networks, humans are no longer the absolute center of social construction, and cinema can be a critical medium to dismantle the tension between human agency and algorithms